2012
DOI: 10.1080/19425120.2012.675982
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Size, and Origin of Juvenile Chinook Salmon in Shallow‐Water Habitats of the Lower Columbia River and Estuary, 2002–2007

Abstract: We monitored fish assemblages monthly at estuarine and tidal freshwater sites in the lower Columbia River and estuary from January 2002 through September 2007 in order to identify specific salmon stocks and migration stages that may benefit from habitat restoration initiatives. We report landscape‐scale and seasonal variation in abundance, size, hatchery production (based on adipose fin clips), and genetic stock of origin of juvenile Chinook salmon Oncorhynchus tshawytscha. From fish implanted with coded wire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
94
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(104 citation statements)
references
References 37 publications
8
94
1
Order By: Relevance
“…Similarly, Quinones and Mulligan (2005) reported that juvenile Chinook Salmon densities were greater in the middle and upper reaches (including tidal freshwater) of the Smith River estuary (California) than in the lowest segments. Although our study areas (centered at rkm 125 and 195) were segregated by greater distances than those sampled by Roegner et al (2012) and Quinones and Mulligan (2005), the two areas did not differ in salmon density or in the proportional representation of sizeclasses among unmarked Chinook Salmon. Temporal trends in Chinook Salmon size in our study and that of Roegner et al (2012) were similar; fry were predominant during winter and spring, and fish size generally increased with time.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Similarly, Quinones and Mulligan (2005) reported that juvenile Chinook Salmon densities were greater in the middle and upper reaches (including tidal freshwater) of the Smith River estuary (California) than in the lowest segments. Although our study areas (centered at rkm 125 and 195) were segregated by greater distances than those sampled by Roegner et al (2012) and Quinones and Mulligan (2005), the two areas did not differ in salmon density or in the proportional representation of sizeclasses among unmarked Chinook Salmon. Temporal trends in Chinook Salmon size in our study and that of Roegner et al (2012) were similar; fry were predominant during winter and spring, and fish size generally increased with time.…”
Section: Discussionmentioning
confidence: 80%
“…Although the environmental conditions (e.g., vegetation and hydrology) resulted in spatial segregation across the LCRE, we did not observe longitudinal "zonation" in the fish community. Across an approximately 60-km expanse of the LCRE, Roegner et al (2012) noted that Chinook Salmon from the tidal freshwater zone (near rkm 60) were more abundant and smaller than those sampled downriver at middle-and lower-estuary sites. Similarly, Quinones and Mulligan (2005) reported that juvenile Chinook Salmon densities were greater in the middle and upper reaches (including tidal freshwater) of the Smith River estuary (California) than in the lowest segments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In light of these differences, future research efforts investigating the effects of hatchery programs on rebuilding threatened Columbia River salmon populations (e.g., Paquet et al 2011) should evaluate ecological interactions between hatchery-and naturally produced fish in estuarine and nearshore ocean habitats (Fresh 1997;Rand et al 2012). Furthermore, the extent to which fine-scale habitat use patterns observed in this part of the estuary apply to reaches further upstream is unclear (Roegner et al 2012;Teel et al 2014;Sather et al 2016); additional research is needed to elucidate patterns of habitat use elsewhere in the system. Finally, our data can also guide the design of restoration actions for multiple salmon stocks and runs in the Columbia River estuary and can inform the potential benefits of such efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Catches were processed according to standard protocols (Roegner et al 2012;Weitkamp et al 2012). Juvenile salmon were anesthetized (tricaine methanesulfonate), identified to species, and measured to the nearest millimeter FL.…”
Section: Methodsmentioning
confidence: 99%